FAMILY TAKAFUL: IT’S ROLE IN SOCIAL ECONOMIC DEVELOPMENT AND AS A SAVINGS AND INVESTMENT INSTRUMENT IN MALAYSIA – AN EXTENSION - Abdul Rahman, Zuriah (Jurnal Syariah, 2008)
This study has dual objectives: first, to investigate whether any relationships exist between the macro economic variables and the demand for family takaful (Islamic life insurance) in Malaysia. Second, to examine whether the establishment of takaful institutions has produced a positive social economic impact in Malaysia as measured by the economic indicators. Islamic life insurance or family takaful, is a form of savings instrument that is popular among Malaysian Muslims in general and has its appeal due to its shari‘ah compliant attributes compared to conventional life insurance products. This study found that from the time of inception, Takaful Malaysia and Takaful Nasional in 1984 and 1994 respectively, their existence has had a healthy impact on the socio economy of the country. This is attested by the effect that the positive employment increment and its profit before tax and zakat (tithe) has on the economy. Being the pioneer in offering shari‘ah compliant insurance products, Takaful Malaysia’s profit performance and its capacity to generate new business in the form of premium or contribution is directly affected by the macro-economic variables, as measured by Malaysia’s gross domestic product, consumer price index and treasury bills or short-term interest rates. If this trend continues, then it is signalling to the government the necessity to provide a conducive economic environment that will ensure this business activity continues to flourish in Malaysia. Lastly, it is common knowledge that 90 percent of the Muslim market, comprising the indigenous race or Malays, have not purchased any form of life insurance or family takaful, thus, it is pertinent that the Central Bank of Malaysia, the regulatory body of financial institutions in Malaysia, considers issuing new licences to would-be takaful operators to provide a wider offering of takaful products that would appeal to this untapped market.